Lipid Profile of Women with Polycystic Ovary Syndrome Attending a Tertiary Care Hospital of Dhaka City (Ibrahim Medical College Journal, 2016)
Polycystic ovary syndrome (PCOS) is one of the common disorders in women at child bearing age. The purpose of the present study was to investigate the lipid profile in patients with polycystic ovary syndrome. A total of 103 women with PCOS of 15-36 years of age were included in the present study. Of the 103 PCOS women, 50% were overweight or obese, 29.1% had impaired glucose tolerance (IGT) and 4.9% had type2 diabetes mellitus (T2DM). The mean BMI was generally higher (25.8±5.5 kg/m2). The mean serum cholesterol levels ranged from182 mg/dl to 236 mg/dl in all groups of women. The results of our study showed that women with PCOS had altered lipid profile and glycemic status. Therefore, evaluation of metabolic status is necessary for better management of women with PCOS.Ibrahim Med. Coll. J. 2014; 8(2): 47-49